The Effect of Biology Learning on Increasing Students' Scientific Literacy: A Review - Mulyani, Irna (Balai Publikasi Indonesia, 2023)
This study is a literature review which aims to identify the most effective learning model for improving students' scientific literacy skills in biology learning. 25 articles were obtained from search results on Google Scholar that met the relevant criteria for review. The results of a review of 25 articles show that there are many learning models that can be used to improve scientific literacy skills. The most effective learning model in increasing scientific literacy is Contextual Teaching and Learning (CTL).